2013
DOI: 10.1177/0748233713487247
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of neurotoxic and immunotoxic effects of some plant growth regulators at subacute and subchronic applications on rats

Abstract: The present study was aimed to investigate the effects of subacute and subchronic treatment of some plant growth regulators (PGRs), such as abscisic acid (ABA) and gibberellic acid (GA3), on neurological and immunological biomarkers in various tissues of rats. The activities of acetylcholinesterase (AChE) and butrylcholinesterase (BChE) were selected as biomarkers for neurotoxic biomarkers. Adenosine deaminase (ADA) and myeloperoxidase (MPO) were measured as indicators for immunotoxic investigation purpose. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Administration of very high doses of ABA is well tolerated in mice without adverse effects (Li et al, 2011), which makes ABA treatments pharmacologically interesting. There are however reports that long-term ABA exposure might have adverse effects (Isik and Celik, 2015), which calls for caution. ABA treatment in humans and animal models has been suggested to be beneficial for type 2 diabetes (Guri et al, 2007; Bruzzone et al, 2015; Magnone et al, 2015), inflammatory bowel disease (IBD) (Guri et al, 2011; Viladomiu et al, 2013), atherosclerosis (Guri et al, 2010), systemic sclerosis (Bruzzone et al, 2012c), glioma (Zhou et al, 2016), depression (Qi et al, 2015b, 2016), and resistance against hepatitis C (Rakic et al, 2006), influenza (Hontecillas et al, 2013), malaria (Glennon et al, 2016), and mycobacteria (Clark et al, 2013).…”
Section: Physiological and Pharmacological Effects Of Aba In Animalsmentioning
confidence: 99%
“…Administration of very high doses of ABA is well tolerated in mice without adverse effects (Li et al, 2011), which makes ABA treatments pharmacologically interesting. There are however reports that long-term ABA exposure might have adverse effects (Isik and Celik, 2015), which calls for caution. ABA treatment in humans and animal models has been suggested to be beneficial for type 2 diabetes (Guri et al, 2007; Bruzzone et al, 2015; Magnone et al, 2015), inflammatory bowel disease (IBD) (Guri et al, 2011; Viladomiu et al, 2013), atherosclerosis (Guri et al, 2010), systemic sclerosis (Bruzzone et al, 2012c), glioma (Zhou et al, 2016), depression (Qi et al, 2015b, 2016), and resistance against hepatitis C (Rakic et al, 2006), influenza (Hontecillas et al, 2013), malaria (Glennon et al, 2016), and mycobacteria (Clark et al, 2013).…”
Section: Physiological and Pharmacological Effects Of Aba In Animalsmentioning
confidence: 99%
“…The large-scale use of PGRs began in the 1930s, and since then, the research and application of PGRs have become an indispensable part of modern agricultural production in the world [22]. However, if the application times are not correct, or if the wrong concentration is used, especially indiscriminate and excessive use of PGRs, the residue of PGRs can occur in plants, soils, and underground water, leading to adverse effects on agricultural products and public health [23,24]. Even at trace levels, PGR residues can still threaten human health such as early maturity, carcinogenicity, reproductive impairment, immunotoxicity, neurotoxicity, and acute toxicity [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Although studies showed that residues of phytohormones when using in production or in the field can affect environmental pollution, the development of animal, human health problems, and food poisoning if using them was not corrected the producer's instruction [13,14] . Thus, the high residue of phytohormones in food can lead to toxicity to organs such as liver, kidney, neurosystem, fluctuate antioxidant defense system or even induce cancers [15][16][17] . Therefore, maximum residues limits of phytohormones have been controlled by international and national laws not only to monitor and regulate phytohormone residues in food but also to ensure the food safety.…”
Section: Introductionmentioning
confidence: 99%